From symbolism to substance: evaluating state disclosure laws and the case for federal oversight - Cheng, Sherri; Duan, Wenjing; Zhou, Wenqi (Frontiers in Health Services, 2025)
Pharmaceutical payments to physicians have long raised concerns about conflicts of interest and rising healthcare costs. While the Physician Payments Sunshine Act (PPSA) established federal transparency standards in 2013, several states had already enacted their own disclosure laws. This study evaluates the hypothesis that individual state policies varied in effectiveness at shaping corporate payment strategies. Specifically, we examined four state policies, Massachusetts (MA), Maine (ME), Minnesota (MN), and West Virginia (WV), using a difference-in-differences design, comparing the outcomes with matched control states before and after PPSA implementation. We analyzed meals and travel payments from four major pharmaceutical companies using ProPublica's Dollars for Docs (2012–2013) and Centers for Medicare & Medicaid Services’ Open Payments (2014–2015) data. Results indicate that MA's comprehensive policy, featuring strict reporting requirements, public accessibility, and enforcement, yielded a significant 44% decline in travel payments. In contrast, ME, MN, and WV's policies showed negligible impacts. These findings suggest that disclosure laws exert real influence only when they are comprehensive, transparent, and backed by enforcement. This underscores the critical role of policy structure in addressing conflicts of interest and points to ways the PPSA framework could be strengthened. Based on our findings, we suggest that other nations could strengthen their systems by adopting centralized and standardized reporting systems, similar to the PPSA.